Analisis Case Based Reasoning (CBR) Diagnosa Kerusakan Lift Berdasarkan Error Inverter Nice-3000 - Alfian Ammar Farhan; Maulana Muhamad Sulaiman (CV. Multi Kreasi Media, 2024)
This research was conducted with the aim of analyzing as well as applying the case based reasoning (CBR) method in diagnosing damage to elevators using similarity calculations. The analyzed data was obtained from PT. Leuser Tri Sakatama results from interviews, observations and literature studies with the permission of Mr. Agung Suparwi as the president director of PT. Leuser Tri Sakatama. The project owned by PT. Leuser Tri Sakatama which is located in JABODETABEK as many as 78, elevator damage data for 2020-2021 as much as 177 damage data. Based on the results of the research, the implementation of the case based reasoning (CBR) method using similarity calculations to find the largest percentage in diagnosing damage to the elevator has been completed. The database has been designed with 3 tables, namely the error code table, the project list table and the elevator damage table for 2020-2021.